Mapping of the Complement C9 Binding Region on Clonorchis sinensis Paramyosin - Kang, Jung-Mi; Lê, Hương Giang; Võ, Tuấn Cường; Yoo, Won Gi; Sohn, Woon-Mok; Na, Byoung-Kuk (Korean journal of parasitology, 2022)
Heliminthic paramyosin is a multifunctional protein that not only acts as a structural protein in muscle layers but as an immune-modulatory molecule interacting with the host immune system. Previously, we found that paramyosin from Clonorchis sinensis (CsPmy) is bound to human complement C9 protein (C9). To analyze the C9 binding region on CsPmy, overlapping recombinant fragments of CsPmy were produced and their binding activity to human C9 was investigated. The fragmental expression of CsPmy and C9 binding assays revealed that the C9 binding region was located at the C-terminus of CsPmy. Further analysis of the C-terminus of CsPmy to narrow the C9 binding region on CsPmy indicated that the region flanking731Leu–780 Leu was a potent C9 binding region. The CsPmy fragments corresponding to the region effectively inhibited human C9 polymerization. These results provide a precise molecular basis for CsPmy as a potent immunomodulator to evade host immune defenses by inhibiting complement attack.